TEACHING ENGLISH WITH TIK TOK: A CONTENT ANALYSIS OF #LEARNINGENGLISHWITHMRFAISAL - Hartono (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The rise of social media platforms like TikTok has created new avenues for informal language learning. This study employs a qualitative content analysis to investigate the pedagogical strategies within the popular Indonesian TikTok hashtag #learningenglishwithmrfaisal. The research aims to identify the types of English language content, teaching strategies, and pedagogical approaches used by the creator, Mr. Faisal. A systematic analysis was conducted on a purposive sample of 10 public TikTok videos from the hashtag. Data collection involved video observation, transcription, and documentation of multimodal elements, followed by a thematic analysis. Key findings reveal a primary focus on pronunciation drills and practical vocabulary, delivered through highly repetitive and multimodal techniques. Mr. Faisal effectively combines verbal repetition, visual cues (on-screen text, mouth close-ups), exaggerated facial expressions, and motivational speaking to facilitate learning and maintain engagement. The study concludes that TikTok serves as a significant platform for informal digital language learning, particularly for micro-learning and confidence-building. These findings suggest that formal educators can adopt similar engaging, bite-sized techniques, while content creators can leverage multimodal design to enhance instructional video effectiveness.